"Which Child Left Behind": Historical Issues Regarding Equity in Science Assessment - J. Joy Cumming; Peter J. Fensham (MDPI AG, 2013)
Assessment of learning plays a dominant role in formal education in the forms of determining features of curriculum that are emphasized, pedagogic methods that teachers use with their students, and parents' and employers' understanding of how well students have performed. A common perception is that fair assessment applies the same mode of assessment and content focus for all students-the approach of assessments in international comparative studies of science achievement. This article examines research evidence demonstrating that the act of assessment is not neutral-different forms of assessment advantage or disadvantage groups of students on the basis of family backgrounds, gender, race, or disability. Assessment that implicitly or explicitly captures the social capital of the child serves to consolidate, not address, educational equity. The article provides an overview of ways that science curriculum focus and assessment can introduce bias in the identification of student achievement. It examines the effect of changes to curriculum and assessment approaches in science, and relationships between assessment of science and the cultural context of the student. Recommendations are provided for science-assessment research to address bias for different groups of students.